Low-dose exposure to triclosan disrupted osteogenic differentiation of mouse embryonic stem cells via BMP/ERK/Smad/Runx-2 signalling pathway. (May 2019) - Cheng, Wei; Yang, Shoufei; Liang, Fan; Wang, Wei; Zhou, Ren; Li, Yan; Feng, Yan; Wang, Yan
Abstract: Triclosan (TCS) has been used widely in personal care products for its broad-spectrum antimicrobial activity. The detection of TCS in the umbilical cord sera, amniotic fluid, and placenta, has raised concerns about the risk to foetal development. In the current study, the embryonic stem cells test (EST) were utilized primarily for the evaluation of the adverse effects of TCS on cardiogenesis and osteogenesis in vitro . TCS was predicted to be weakly embryotoxic in cardiogenesis and strongly embryotoxic in osteogenesis. The 50% inhibition value of osteogenic differentiation was 110 times lower than that of cardiac differentiation, which suggested that the development of the skeletal system was more sensitive to TCS-induced disruption. The mechanism through which TCS exerted toxicity on osteogenesis was studied further. Decreased calcification in ESC-derived osteoblasts was observed after exposure to TCS at a low dose, equal to the human internal exposure level. TCS was observed to specifically target ERK activation, rather than JNK or p38. Further, the downregulation of p-Smad-1, together with strong inhibition on Runx-2 and Bglap-2 expression, was observed via BMP/ERK/Smad signalling when cells were exposed to TCS. The change in Runx-2 induced by a low-dose TCS highlighted a specific target for exploring its adverse effect on skeletal development. Highlights: Mouse ESC derived organ-specific cells were applied for studying toxicity of TCS. TCS-induced osteogenic toxicity sensitively as compared to its cardiac toxicity. Low dose of TCS hampered the skeletal development in vitro via ERK/BMP-Smad signalling pathway. The low dose was equal to the human internal exposure level of TCS.